2020
DOI: 10.3390/ijms21197063
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery of a GCDH Variant Associated to Severe Deflavinylation—Molecular Insights into Potential Beneficial Effects of Riboflavin Supplementation in Glutaric Aciduria-Type I Patients

Abstract: Riboflavin is the biological precursor of two important flavin cofactors—flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN)—that are critical prosthetic groups in several redox enzymes. While dietary supplementation with riboflavin is a recognized support therapy in several inborn errors of metabolism, it has yet unproven benefits in several other pathologies affecting flavoproteins. This is the case for glutaric aciduria type I (GA-I), a rare neurometabolic disorder associated with mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Also, the P248L variant is associated with some residual GCDH activity in other patients. In addition, in the p.Val400Met homozygous mutation study, riboflavin was reported to be a driving force for the mutant enzyme [ 23 ]. These results provide principal proof for the beneficial effects of riboflavin in GA-I.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the P248L variant is associated with some residual GCDH activity in other patients. In addition, in the p.Val400Met homozygous mutation study, riboflavin was reported to be a driving force for the mutant enzyme [ 23 ]. These results provide principal proof for the beneficial effects of riboflavin in GA-I.…”
Section: Discussionmentioning
confidence: 99%